Ecotoxicity Emissions of Corn Production - Wolf, Allison (My University, 2025)
The population continuously rises throughout the world. As the that number continues to rise, so will the need for crops. The growth of the agricultural market will require an increase in herbicide, fertilizer, and irrigation, especially in the Midwest where higher yields are achieved with higher agrochemical application and irrigation. For an environmentally friendly increase in crops, it is important for farmers to identify and explore agricultural techniques that result in maximum yields with minimum impact. The Testing Ag Performance Solutions (TAPS) program allows for farmers to experiment with irrigation and farming practices while participating in a farm management competition. This Honors Project analyzes the ecological toxicity impacts for corn production over 34 differently managed TAPS fields and assesses the inputs of herbicides and fertilizers. The impacts were assessed using USEtox characterization factors from TRACI 2.0 and the impact category analyzed was ecotoxicity, which is generally overlooked in corn production analyses. TAPS data was analyzed using a reference seed/seeding rate and variable seed/seeding rates determined by the farmer. It was found that the ecotoxicity of corn production for agricultural soil ranged from 15.51 to 31.22 CTUeco/kg corn for reference seed/seeding rate and 13.54 to 37.02 CTUeco/kg corn for variable seed/seeding rate. Ecotoxicity for freshwater was generally higher, ranging from 49.39 to 99.37 CTUeco/kg corn for reference seed/seeding rate and 43.09 to 117.87 CTUeco/kg corn for variable seed/seeding rate. Finally, the ecotoxicity for air ranged from 19.09 to 38.43 CTUeco/kg corn for reference seed/seeding rate and 16.66 to 45.57 CTUeco/kg corn for variable seed/seeding rate. Results showed that the largest contributor to ecotoxicity was fertilizer for agricultural soil with 68%, herbicide for freshwater with 80%, and fertilizer for air with 93%. Results for irrigation vs yield showed that for 6 to 6.75 inches of total irrigation, the produced yield was very similar to that of 6.75 to 10 inches. Total ecotoxicity and nitrogen input did not show consistent trends. This report shows that corn production can have significant ecotoxicity impacts, though usually overlooked within studies. Finding sustainable irrigation and farming practices can potentially reduce these impacts while keeping a desired yield.